Pengaruh Putaran Spindel Terhadap Kekerasan Permukaan Baja Karbon pada Proses CNC Turning - Adi Febrianton; Indah Purnama Putri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
CNC machines are computer-controlled machines that can understand the N and G codes (Gcodes) that regulate the machine tool system, (program motion pointers using numbers and letters to cut rotating workpieces), the machine works according to code commands. The code programme used is G75 for the groove making process and G97 for the CNC Turning process. The research aims to determine the variation of spindle rotation on S45C carbon steel. The speed variations used are 1266 rpm, 1066 rpm, 866 rpm. With a depth of cut of 0.4 mm and a feeding of cut of 0.15 mm and the insert used is an insert with the Iscar brand. The average value results obtained from the testing process using a roughness test tool (stylus). The lowest roughness value at 1266 rpm spindle rotation is included in the roughness class, namely N7. The highest roughness value at 866 rpm spindle rotation is included in the roughness class, namely N8. While the intermediate roughness value at 1066 rpm spindle rotation is included in the N7 roughness class. The effect of roughness results on objects, namely, the higher the spindle rotation, the lower the value of the roughness results, on the contrary, the lower the spindle rotation, the rougher the roughness value in the turning process.